If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 * 6 + -12 = 5x + m Multiply 7 * 6 42 + -12 = 5x + m Combine like terms: 42 + -12 = 30 30 = 5x + m Reorder the terms: 30 = m + 5x Solving 30 = m + 5x Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. 30 + -1m = m + -1m + 5x Combine like terms: m + -1m = 0 30 + -1m = 0 + 5x 30 + -1m = 5x Add '-30' to each side of the equation. 30 + -30 + -1m = -30 + 5x Combine like terms: 30 + -30 = 0 0 + -1m = -30 + 5x -1m = -30 + 5x Divide each side by '-1'. m = 30 + -5x Simplifying m = 30 + -5x
| 10s-40=-94 | | y(2y-5)=12 | | a*(t+z)=45*z+67 | | 6m+54=17 | | 9b-2= | | -c-4=1 | | g(r)=8r+4 | | 7+22=133 | | 4(-x+2)+3(x-1)=0 | | (2w+7x+5)(3w-5x)= | | x-3/5+2x=0 | | 5(x+1)=4(x-7) | | -5(3t-2)+2t=4t-3 | | 5(x+1)=(x-7) | | x(3x+2)+x(x+6)=7+x(4x+1) | | 12x+4=7x-30+4 | | 5+2(x+3)=10 | | 30x-4x=12-7x | | 7e^3x+2=27 | | 16x+y=80 | | X-(16/x)=6 | | 2x-(x-5)+3(x-1)=12 | | (6n^2-5n^3)+(n^3+5n^2)=0 | | -(2/3)*-5 | | √10/81 | | (6)(-3)+2(55-65)/-5= | | x(y^5+9)+9(y^5+9)= | | q(6-2q)=0 | | 50-30+80=-60 | | 3(u-5)-7=-2(-8u+8)-3u | | 2x^2-33x+108=5123 | | x*.0635=1000 |